Three dimensional finite element analysis of bi-adhesively bonded double lap joint - Ozer, Halil; Oz, Ozkan (ELSEVIER SCI LTD, 2012)
Hybrid-adhesive joints are an alternative stress reduction technique for adhesively bonded joints. The joints have two types of adhesives in the overlap region. The stiff adhesive should be located in the middle and flexible adhesive at the ends. In this study, the effect of the hybrid-adhesive bondline on the shear and peeling stresses of a double lap joint were investigated using a three-dimensional finite element model. We developed a three dimensional model of the double lap joint based on solid and contact elements. Contact problem is considered to model the interface as two surfaces belonging to adherend and adhesive. Finite element analyses were performed for four different bond-length ratios (0.2,0.4,0.7 and 1.3). The results show that the stress components can be optimized using appropriate bond-length ratios. To validate the finite element analysis results, comparisons were made with available closed-form solutions. The numerical results were found in good agreement with the analytical solutions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Finite element stress analysis; Stress distribution; Joint design; PERFORMANCE; Engineering; Materials Science